PENGARUH DANA ALOKASI UMUM DAN PENDAPATAN PAJAK DAERAH TERHADAP ALOKASI BELANJA DAERAH - Sinaga, Nita Karlina; Tipa, Handra (SCIENTIA JOURNAL, 2019)
ABSTRACT Regional Expenditure Allocationais a unity of budget. One time sector that could have the opportunity to finance RegionalaExpenditure is theaGeneral AllocationaFund and Local TaxaRevenue. Therefore, theaappropriate researchato find outawhether theaGeneral AllocationaFund, And IncomeaTax Regionasignificantly toathe Allocationaof Regional Expenditure. Population and sample of this research is using multiple linear regression analysisausing data generated fromasummary of report of realization of Revenue and Expenditure (APBD). Where in theasampleaselection menggunkana technique Full sampling and thearesults of 60 samples of lanyak for analyzed more lanju. The results of this study proved the General Allocation Fund and Local Tax Income beperngaruh significant to the RegionalaExpenditure Allocation in Batam, This is explained inathe value of R Square is 0.842 this berate 84.2% of the dependent variable Budget Allocation of RegionalaExpenditureacan beaexplained byavariations of variables independekaDana Alokasi Umum , and Local Tax Revenue . Whileathe rest 15,8 by other factors. Varsial Variable Result of GeneralaAllocation FundaandaIncome Tax of disaster area significanato Allocation of RegionalaExpenditure.